The practice of social research - Babbie, Earl R. (Thomson/Wadsworth, 2007)
"Although it was initially written for sociology courses, [this book can be] used in fields such as Psychology, Public Administration, Urban Studies, Education, Communications, Social Sciences, and Political Science ...-Pref. [In this book] you will learn the logic and skills necessary to do research effectively - and the step-by-step process for writing reports. You'll gain a real understanding of quantitative and qualitative methods and inductive and deductive distinctions. [The author] makes abstract theory understandable with humor, down-to-earth metaphors, and many contemporary examples ... [This] edition adds new information on doing online research and expanded coverage of statistical techniques"-Back cover